Sleeping Beauty - Southgate, vera (London : Lady bird Ltd)
A king is protective of his beautiful daughter, the princess. An evil fairy curses the princess, pronouncing that she will die when she is pricked by a spindle. However, a good fairy manages to intervene so that the prophecy is softened: the princess will not die if she is pricked with a spindle, but she will fall unconscious for a hundred years. The king bans flax and spinning equipment from his palace, so as to protect his daughter from such a fate.
Fiction English book
Keywords: English - Fiction Book